2004
DOI: 10.1080/17461390400074204
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Habits and Fluid Intake of a Group of Elite Spanish Basketball Players: A Need for Professional Advice?

Abstract: The aim of the present study was to analyse dietary habits and fluid intake of professional basketball players with consideration of dietary guidelines and sport nutrition recommendations. A dietary habit questionnaire including a 24 h recall was recorded by 55 elite basketball players of the first Spanish Basketball League. Energy consumption among these athletes was high 17.7 ± 0.9 MJ • day -1 in comparison to other elite team sport athletes. Furthermore intakes of protein, fat, saturated fatty acids mineral… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
30
1
5

Year Published

2009
2009
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(40 citation statements)
references
References 39 publications
4
30
1
5
Order By: Relevance
“…The difference between groups was not significant when the estimated energy intake was expressed relative to body weight (51 vs. 45 kcal/kg/d, p = .052). Similar relative energy intakes were observed in US football players (15 to 18 years) and elite Spanish basketball players (mean age 25.1 years; 48 and 47 kcal/kg/d, respectively; Petrie et al, 2004, Schroder et al, 2004.…”
Section: Discussionsupporting
confidence: 80%
“…The difference between groups was not significant when the estimated energy intake was expressed relative to body weight (51 vs. 45 kcal/kg/d, p = .052). Similar relative energy intakes were observed in US football players (15 to 18 years) and elite Spanish basketball players (mean age 25.1 years; 48 and 47 kcal/kg/d, respectively; Petrie et al, 2004, Schroder et al, 2004.…”
Section: Discussionsupporting
confidence: 80%
“…Along these lines, another study with elite futsal players [37] obtained an average of 800 mL intake after a training session, less than the total fluid intake by our players. In other team sports, Schröder et al [38] assessed fluid intake during training and competition in 55 elite basketball players, which mean result was 882 ± 486 mL, less than that obtained in our study.…”
Section: Discussioncontrasting
confidence: 53%
“…2017, 9(6S), 1024-1040 1034 on sports drink consumption during high intensity exercise for more than 1 h and less intense exercise sustained for longer period, water was regarded as the best drink by these individuals and was the most preferred beverage to be consumed by the participants during exercise. This result is supported by the work of Schroder et al [15] who conducted a survey on dietary habits and fluid intake of the elite Spanish basketball players and observed that water was the preferred beverage consumed by the participants during training (92%) and competition (88%). If people regularly exercise for more than 1 h at high intensity or less intense but sustained for a longer period, sports drinks may be a better option for fluid and fuel replacement during exercise because sodium and carbohydrate contents help to increase physiological drive to drink to replace sweat losses and to maintain blood glucose level, respectively [13].…”
Section: Discussionsupporting
confidence: 72%